Kohesi Gramatikal dan Kohesi Leksikal dalam Cerita Anak Berjudul "Buku Mini Dea" Karya Watiek Ideo dan Yuli Rahmawati - Ardiyanti, Devi; Setyorini, Ririn (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
This study uses descriptive research methods. The data in this study are qualitative data in the form of words, phrases, clauses, or sentences in the form of lexical and grammatical cohesion in the short stories of Mini Books Dea Karya Watiek Ideo and Yuli Rahmawati. The source of the data in this study is the discourse of the short stories Mini Book of Watiek Ideo and Yuli Rahmawati. The technique used to collect data in this research is documentation technique. Data processing techniques in this study use qualitative analysis. The results and discussion show that the short story entitled Mini Dea Books by Watiek Ideo and Yuli Rahmawati found grammatical cohesion and lexical cohesion. The grammatical cohesion found is substitution (replacement), subordinate conjunctions of ways, subordinate conjunctions of causes, personal references, anaphorical references, demonstrative references, coordinative conjunctions, subordinate conjunctions, conjunctions between sentences. The lexical cohesion found was epistrofa repetition and antonyms.Keywords: children's story; cohesion; grammatical cohesion; lexical cohesion.